Burnout in agile software development - Zdeněk Vafek (Acta Polytechnica CTU Proceedings)
This article examines the relationship between personality traits measured by the HEXACO model and the prevalence of burnout syndrome as measured by the Maslach Burnout Inventory (MBI). The research was conducted on a sample of nine developers working in the IT sector, who were divided into two groups according to project management methods – the agile Scrum methodology and the traditional waterfall approach. The aim of the study was to determine whether the implementation of the Scrum method can contribute to reducing the risk of burnout and how individual personality traits correlate with selected dimensions of burnout syndrome. The results show that individuals with higher extraversion and conscientiousness show lower levels of emotional exhaustion and depersonalization, while honesty-humility and agreeableness have less influence on burnout syndrome. At the same time, the introduction of the Scrum methodology contributed to better work stress management and work organization in most cases. The results are limited by the small sample size, but they can provide valuable insights for further research as a pilot study.